2019
DOI: 10.1155/2019/7143989
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening of Essential Oils and Antibacterial Activity and Antioxidant Properties of Barringtonia asiatica (L) Leaf Extract

Abstract: Objective. To ascertain the essential oil phytochemicals of the leaf and to test for the antibacterial and antioxidant properties of dichloromethane crude extract of Barringtonia asiatica leaf. Methods. The phytochemical screening of essential oils, extraction by hydrodistillation using the Clevenger apparatus, and analysis performed by gas chromatography equipped with a flame ionization detector (GC-FID). Antibacterial activity and the inhibition rate (mm) were determined using the agar disc method against fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Several lines of scientific studies suggested that the essential oils exerted higher antimicrobial activity against gram-positive bacteria, compared to the gram-negative bacteria. However, our study showed that ALEO, at the concentration of 100 μl/mL, was active against both Gram-negative and -positive bacteria [5,39]. From time immemorial, there has been an erroneous belief that herbal remedies or their semi-synthetic derivatives were free of any toxic effects [40].…”
Section: Biochemical Analysesmentioning
confidence: 77%
See 1 more Smart Citation
“…Several lines of scientific studies suggested that the essential oils exerted higher antimicrobial activity against gram-positive bacteria, compared to the gram-negative bacteria. However, our study showed that ALEO, at the concentration of 100 μl/mL, was active against both Gram-negative and -positive bacteria [5,39]. From time immemorial, there has been an erroneous belief that herbal remedies or their semi-synthetic derivatives were free of any toxic effects [40].…”
Section: Biochemical Analysesmentioning
confidence: 77%
“…A myriad of biological activities has been attributed to essential oils extracted from the flowers, leaves, stems, and roots of aromatic plants. Specifically leaf-derived essential have been studied for antibacterial [4,5], antioxidant [6,7], antifungal [8], anti-diabetic [9], anti-cancer [10,11] ; anti-parasitic [12,13], anti-aging [14], anti-inflammatory [15] and hepatoprotective [16,17] effects. The components and functional groups of the essential oils contribute to their bio-activities.…”
Section: Introductionmentioning
confidence: 99%
“…Four microbial isolates drawn from the list of common and emerging nosocomial pathogens were used in the study [25,26]. M. smegmatis 155 mc 2 laboratory strain was obtained from the Department of Clinical Laboratory Sciences, University of Cape Town. A clinical strain of C. krusei and K. pneumoniae (ATCC 700603) was obtained from the Department of Medical Microbiology, University of Zimbabwe.…”
Section: Growth Of Microbial Cellsmentioning
confidence: 99%
“…Infectious diseases remain the major cause of morbidity and mortality especially in the developing countries [1]. Resistance to common antimicrobial agents has led to high frequency of treatment failures and increase in treatment cost [2].…”
Section: Introductionmentioning
confidence: 99%
“…Biohazard cabinet was used for the inoculation of the bacteria [15]. 1 mL of the prepared broth was streaked over the entire agar plate surface in four different directions using sterile cotton bud.…”
Section: Plate Inoculationmentioning
confidence: 99%